(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The history of the book is marginal in the textual framework of the textbook and generally appears intertwined in a few narrative lines of other themes that encompass them and that belong to political and socio- economic rather than cultural spheres. Despite the peripheral location in the discursive spatiality of school textbooks, we detect the book as an object of analysis in itself. There are only two publishing houses that incorporate it as a subject of study, Puerto de Palos and Estrada, both of national origin. This largely explains the minimal but existing freedom that these publishers have, to the detriment of international ones that plan content for broader markets.